Performance and adoption factors for open pollinated and hybrid maize varieties: Evidence from farmers’ fields in northern Ghana - van Asselt, Joanna; DI Battista, Federica; Kolavalli, Shashidhara; Udry, Christopher R.; Baker, Nate (International Food Policy Research Institute, 2018)
Maize is the most widely grown starch in Ghana, and yet domestic supply does not meet demand, because maize productivity is low. Trials were performed in northern Ghana in 2015 to determine whether hybrid varieties would outperform the varieties planted by farmers and, therefore, increase maize productivity. Two foreign hybrids performed consistently better then Obaatanpa, the most widely used variety in the north. In 2016, Adikanfo, the best performing hybrid, and certified Obaatanpa were made available for purchase at subsidized rates in the communities where the 2015 trials had been conducted. A survey was then carried out to study whether the trials had any effect on technology uptake or behavioral change among farmers in the region and if the varieties performed as well on the farmers’ fields as in the trials. This paper presents the descriptive results of the survey.